1968
DOI: 10.1063/1.1670050
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of Acetonitrile and Acetonitrile-d3

Abstract: The infrared spectra of acetonitrile and acetonitrile-d3 have been studied at − 50°C for the high-temperature (β) crystalline phase and at − 65°, − 115° and − 192°C for the low-temperature (α) crystalline phase. A powder x-ray pattern obtained at liquid-nitrogen temperature indicates that the unit cell is primitive orthorhombic and that it contains eight molecules. It is shown that the consideration of all available structural data together with the site group and factor group splittings for the α crystal tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
68
2
1

Year Published

1973
1973
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 9 publications
11
68
2
1
Order By: Relevance
“…The sample phase had to Bray 1958). Calorimetric measurements confirmed two distinct crystalline phases (low-temperature Ͱ and high-tem-be maintained at about 210 K for 1 hr to obtain the lowtemperature phase (Pace and Noe 1968). Because the anperature ͱ) with a transition temperature of 216.9 K, which nealing temperature of 210 K needed to obtain the Ͱ phase concluded that the crystal structure could be monoclinic, tetragonal, or trigonal (Milligan and Jacox 1962).…”
mentioning
confidence: 90%
“…The sample phase had to Bray 1958). Calorimetric measurements confirmed two distinct crystalline phases (low-temperature Ͱ and high-tem-be maintained at about 210 K for 1 hr to obtain the lowtemperature phase (Pace and Noe 1968). Because the anperature ͱ) with a transition temperature of 216.9 K, which nealing temperature of 210 K needed to obtain the Ͱ phase concluded that the crystal structure could be monoclinic, tetragonal, or trigonal (Milligan and Jacox 1962).…”
mentioning
confidence: 90%
“…This is suggestive of hydrogen bonding even though the intermolecular bond is only slightly less than the sum of the van der Waals radii. Barrow was not able to grow a single crystal of the low temperature phase and our knowledge of this phase is based on the spectroscopic studies mentioned above and a powder X-ray study included in the paper by Pace and Noe [4]. Both Pace and Noe [4] and Marzocchi and Migliorini [5] favoured a structure with factor group D2h and eight molecules in a unit cell sitting on two sets of sites with Cs symmetry.…”
Section: Introductionmentioning
confidence: 96%
“…Barrow was not able to grow a single crystal of the low temperature phase and our knowledge of this phase is based on the spectroscopic studies mentioned above and a powder X-ray study included in the paper by Pace and Noe [4]. Both Pace and Noe [4] and Marzocchi and Migliorini [5] favoured a structure with factor group D2h and eight molecules in a unit cell sitting on two sets of sites with Cs symmetry. Anderson and Zeng [6] noted that the Raman and far-infrared spectra of the low temperature phase are simpler than those for the upper phase which is not consistent with the proposed large unit cell.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since the C-N at the transition. The measurements presented here are for interaction is weak, and in most cases relaxation processes samples slowly cooled through the a phase and the samples are very slow, transitions between the N energy levels during will be predominantly b phase (25). In any event, no differthe time scale of the measurement are negligible.…”
Section: Andmentioning
confidence: 97%